Anteseden Brand Trust Maskapai Penerbangan Super Air Jet - Petra Surya Mega Wijaya; Queena Widhya Pamela; Hardono (Jurnal Bisnis Administrasi dan Manajemen, 2026)
In today's era, the world of aviation is no longer a special thing. The choice of the community makes airline companies compete to make their airlines the choice of the public. They will offer prices that are quite attractive to the public by providing some convenience, according to the price of air tickets. This study uses a quantitative method. Quantitative research is an approach that uses numbers in the analysis process. Before starting, it is important to determine the population and sample to be studied. To ensure valid and reliable results, it is necessary to use tools or instruments that have been tested for validity and reliability. Based on the results of data analysis and discussion, it can be concluded that low-cost carriers, customer satisfaction, and flight safety have a significant effect on the brand trust of Super Air Jet airlines. Meanwhile, the airline's performance does not have a significant effect on the brand trust of Super Air Jet.